Political action in machiavellian republicanism - Costa Cerqueira, Marcone (Griot : Revista de Filosofia, 2020)
Our objective in this brief article is guided by the demonstration of the existence of a theory of political action in Machiavelli’s republican thought, with such a theory having its own character that directs it to highlight the action of individuals in the social context. In addition to this objective, we hope to support the thesis that such a theory of political action has a republican scope, not just “republicanist”, in keeping with the Machiavellian preference for institutions that impress on individuals a civic sense based above all on the materiality of political action in the body social. From this assertion, we indicate that our itinerary will be guided by the demonstration of the search for the valorization of political action in Machiavelli’s theory, the materiality of such action, to the detriment of its pure intention, the central focus of Florentine’s work. This disposition of the centrality of political action in Machiavelli republicanism will underscore its appreciation for outlining the political functions of the search for recognition, glory and especially the benefit of the political body as a whole.